Seroprevalence and Associated Risk Factors of Rift Valley Fever in Domestic Small Ruminants in the North Region of Cameroon - R. Poueme; F. Stoek; N. Nloga; J. Awah-Ndukum; M. Rissmann; A. Schulz; A. Wade; J. Kouamo; M. Moctar; A. Eisenbarth; L. God-yang; S. Dickmu; et al. (Veterinary Medicine International)
Rift Valley fever (RVF) is a zoonotic vector borne infectious disease of major medical and veterinary importance particularly in sub-Saharan Africa. However, there is dearth of epidemiological knowledge of the disease in Cameroon. We conducted a cross-sectional study (January 2016–January 2017) to investigate the seroprevalence and potential risk factors of Rift Valley fever virus (RVFV) in sheep and goats in the North region of Cameroon. Stratified sampling approach was used to select herds where sera were collected from 680 randomly selected small ruminants (355 goats and 325 sheep) in eight localities (Kismatari, Lagdo, Pitoa, Garoua, Bocklé, Dembo, Poli and Touboro) within three administrative divisions (Bénoué, Mayo-Rey and Faro) in the North region. Anti-RVFV antibodies were detected using a competitive Enzyme-Linked Immunosorbent Assay (ELISA), while a capture ELISA was used for the detection of specific RVFV-Immunoglobulin M (Ig-M) antibodies. We evaluated the associated potential risk factors of RVF in small ruminants based on observations of animal-related intrinsic and extrinsic factors in combination with serological results. The results revealed that 3.4% (95% confidence interval (CI): 2.2–5.1%) of sampled animals and 24.6% (95% CI: 15.1–37.1%) of 65 sampled herds were seropositive for anti-RVFV antibodies and no difference in seropositivity between sheep and goats at individual animal as well as at herd levels was observed. Localities along hydrographic or large water banks such as Kismatari (OR: 14.333, (95% CI: 1.436–145.088)) and Pitoa (OR = 11.467 (95% CI: 1.249–50.306)) were significantly associated to RVFV antibody seroprevalence in a simple logistic regression. In addition, the multiple regression analysis showed that age and access to water points significantly influenced RVFV antibody seroprevalence in small ruminants. This study revealed that anti-RVFV antibodies are present in sheep and goats in the North region of Cameroon. It highlights the likely endemic circulation of RVFV in the considered localities despite the absence of clinical cases reported in animals or humans. Under these conditions, it is necessary to set up an early warning, surveillance and control strategy based on epizootic risk.